2022
DOI: 10.1002/adma.202108992
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneum‐Inspired Janus Porous Hydrogel with Anti‐Deformation, Anti‐Adhesion, and Pro‐Healing Characteristics for Abdominal Wall Defect Treatment

Abstract: layers has attracted remarkable attention in recent years for surgical challenge and undesirable treatment outcomes. The destruction of the muscular layer is difficult to be sutured and injury of the serosal membrane could induce obvious viscera adhesion. [5,6] In the past few decades, tension-free repair operation is recommended as the standard treatment for soft-tissue defects like abdominal wall defects, in which different types of patches have been widely used. [1,[7][8][9] Traditional synthetic meshes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 77 publications
1
64
0
Order By: Relevance
“…By combining the advantages of film and liquid barriers, the injectable hydrogel can perfectly cover irregular wounds and has shown potential in abdominal adhesion inhibition after open or laparoscopic surgery . Many types of injectable hydrogels with excellent antifouling adhesive capabilities, such as carboxyl-containing dynamically cross-linked supramolecular polymer–nanoparticle hydrogels, Janus hydrogels, , photocurable catechol-grafted hyaluronic acid (HA) hydrogels, , hotmelt tissue adhesives, bottlebrush inspired injectable hydrogels, cellulose-based thermo-gels, and zwitterionic hydrogels, , were prepared by using natural or synthetic polymers through chemical modification or cross-linking. Although efficacy has been shown, these hydrogel systems may encounter at least some of the following limitations: (1) rapid degradation rate and short retention time; (2) presence of toxic residues of cross-linking agents; (3) the use of ultraviolet irradiation; (4) lack of self-healing or self-fused ability to prevent fragmentation during the injection process; (5) slow hydrogel gelation.…”
Section: Introductionmentioning
confidence: 99%
“…By combining the advantages of film and liquid barriers, the injectable hydrogel can perfectly cover irregular wounds and has shown potential in abdominal adhesion inhibition after open or laparoscopic surgery . Many types of injectable hydrogels with excellent antifouling adhesive capabilities, such as carboxyl-containing dynamically cross-linked supramolecular polymer–nanoparticle hydrogels, Janus hydrogels, , photocurable catechol-grafted hyaluronic acid (HA) hydrogels, , hotmelt tissue adhesives, bottlebrush inspired injectable hydrogels, cellulose-based thermo-gels, and zwitterionic hydrogels, , were prepared by using natural or synthetic polymers through chemical modification or cross-linking. Although efficacy has been shown, these hydrogel systems may encounter at least some of the following limitations: (1) rapid degradation rate and short retention time; (2) presence of toxic residues of cross-linking agents; (3) the use of ultraviolet irradiation; (4) lack of self-healing or self-fused ability to prevent fragmentation during the injection process; (5) slow hydrogel gelation.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, a three-layered Janus adhesive with asymmetric wetting properties developed by Xu et al [23] was found to be successful in keeping the wound area dry while absorbing the wound exudate. Other very recent and highly promising examples from this area are peritoneuminspired porous poly(vinyl alcohol) (PVA) hydrogels for canalizing cellular growth at the desired site, [26] and double-layered (ionically and covalently cross-linked) alginate/chitosan films for advanced tendon healing. [25] These asymmetric materials provide a set of distinct functions for the wound-healthy tissue interface.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels have been demonstrated as a class of promising materials that show enticing applications in biomedicine because of their similarity to biological tissues, of which bioadhesive is one of the most important paradigms. The dynamic gel–sol–gel transition would be very interesting for detachable and adaptive adhesives, which matches the concept of self-correction proposed by Cheng and Shi et al For instance, the removal of a wound dressing usually leads to uncomfortable pain and secondary damage to the wound. A gentle gel–sol transition may provide a useful solution for this issue.…”
Section: Resultsmentioning
confidence: 83%